Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/tpj.12694
|View full text |Cite
|
Sign up to set email alerts
|

DYT1 directly regulates the expression of TDF1 for tapetum development and pollen wall formation in Arabidopsis

Abstract: These authors contributed equally to this work. SUMMARYThe tapetum plays a critical role during the development and maturation of microspores. DYSFUNCTIONAL TAPETUM 1 (DYT1) is essential for early tapetal development. Here, we determined that the promoter region (À550 to À463 bp) contains indispensable cis-elements for DYT1 expression. Although DYT1 transcripts can be detected in both meiocytes and tapetal cells, localization of DYT1-GFP demonstrated that DYT1 is strictly located in tapetal cells during micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
119
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 57 publications
0
119
0
Order By: Relevance
“…Previous studies have revealed that DYT1 targets the promoters of MS1 and MYB35 (Feng et al, 2012;Gu et al, 2014). However, our in vivo transcriptional activation assay using the transient transcription assay system (Hellens et al, 2005;Liu et al, 2008) showed that DYT1 alone activates the expression of MS1 and MYB35 only moderately (LUC/REN<10) ( Figures 6A and 6B).…”
Section: Myb35 Expressionmentioning
confidence: 59%
See 2 more Smart Citations
“…Previous studies have revealed that DYT1 targets the promoters of MS1 and MYB35 (Feng et al, 2012;Gu et al, 2014). However, our in vivo transcriptional activation assay using the transient transcription assay system (Hellens et al, 2005;Liu et al, 2008) showed that DYT1 alone activates the expression of MS1 and MYB35 only moderately (LUC/REN<10) ( Figures 6A and 6B).…”
Section: Myb35 Expressionmentioning
confidence: 59%
“…As one of the gatekeeper TFs required for tapetum development, DYT1 is specifically expressed in tapetal cells (Gu et al, 2014). Previously, we showed (Feng et al, 2012) that expression of DYT1 in the cytoplasm as a fusion to the ligand binding domain of the glucocorticoid receptor (GR) failed to rescue the dyt1-1 mutant, with few pollen grains, but the translocation of DYT1-GR into the nucleus due to the treatment with the glucocorticoid hormone analog dexamethasone restores male fertility of ProDYT1:DYT1-GR/dyt1-1 plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CYP703A3, encoding a cytochrome P450 fatty acid hydroxylase, can be regulated by GAMYB and TDR and can be involved in tapetal degradation . In Arabidopsis, DYSFUNCTIONAL TAPETUM1 (Gu et al, 2014), ABORTED MICROSPORES (Xu et al, 2010, and MS1 (Wilson et al, 2001;Ito et al, 2007;Yang et al, 2007) can regulate multiple genes involved in pollen wall development. Thus, we hypothesized that IPE1 indirectly regulates tapetal degeneration via transcription factors.…”
Section: Ipe1 Mediates the Lipid Metabolic Pathway In The Tapetummentioning
confidence: 99%
“…The basic helix-loop-helix (bHLH) transcriptional factor DYSFUNCTIONAL TAPETUM1 (DYT1) is among the earliest acting male-specific regulators and is required for the normal development of tapetum by regulating the normal expression of more than 1,000 anther genes, and dyt1 mutants form abnormal prematurely vacuolated tapetal cells and lack mature pollen (Zhang et al, 2006;Feng et al, 2012;Gu et al, 2014;Zhu et al, 2015). In addition, bHLH010, bHLH089, and bHLH091 together are required for normal tapetum development and transcriptome and pollen fertility, forming both feed-forward and feedback loops with DYT1 (Zhu et al, 2015;Cui et al, 2016).…”
mentioning
confidence: 99%